How can you invert a Taylor serie?(adsbygoogle = window.adsbygoogle || []).push({});

x=y+Ay^2+By^3+Cy^4....

to y=ax+bx^2+cx^3 ...

without the lagrange theorem... must go from x=y+Ay^2+By^3+Cy^4.... to y=ax+bx^2+cx^3 ...

Need help thanks!

**Physics Forums - The Fusion of Science and Community**

# Inverting a Taylor serie

Know someone interested in this topic? Share a link to this question via email,
Google+,
Twitter, or
Facebook

Have something to add?

- Similar discussions for: Inverting a Taylor serie

Loading...

**Physics Forums - The Fusion of Science and Community**